TAKING DISCOVERY IN THE EUROPEAN UNION - de la Rosa, Gloria Esteban (European Scientific Journal, ESJ, 2013)
To foster international cooperation for taking evidence abroad in the new European Space of justice, the Regulation 1206/2001 has open two different ways. But is it not clear enough which is the treatment given to discovery, because it is not a method for obtaining evidence overseas, rather, a procedure put in place to search for the relevant material evidence which will allow the parties to access any information deemed necessary in proving the facts in a case (see above). It should be mentioned Tedesco Case, which never reached the ECJ as the proceedings which gave rise to the prejudicial question had ended (AUTO 27th September 2007). Nevertheless, the Advocate General made a statement in her conclusions: the refusal (by the authority of a member State) of the taking of evidence requested by the European authority was not thought to be justified.